Ghana : An Analysis of Firm Productivity - Teal, Francis; Habyarimana, James; Thiam, Papa; Turner, Ginger (World, Washington, DC, 2013)
The focus of this study is an analysis of firm productivity in Ghana, based on panel of firms surveyed between 1996 and 2002, as well as other information. The analysis focuses on identifying the drivers of productivity and the factors behind the increasing in formalization and the lack of expansion of firms in the Ghanaian private sector. Based on this analysis, the objective is to identify key hypotheses about the investment climate, to be tested in the forthcoming investment climate assessment for Ghana. This hypothesis testing will lead to the identification of priority areas of the investment climate that need to be reformed in order to achieve a higher rate of growth in the private sector and the economy as a whole. It will be argued in this study that more rapid increases in income require an increase both in the rate of investment and, of equal importance, in the returns on that investment. A key element in meeting both those objectives is a shift to private sector investment in export-oriented activities. As recent data for Ghanaian growth shows the growth rate of aggregate investment has been far higher than that for consumption or exports.